Human performance, workload, and situational awareness measures handbook - Gawron, Valerie J. (CRC Press, 2008)
Human performance measurement is the cornerstone of human factors and experimental psychology. This handbook covers the basics of measurement and provides authoritative summaries of over 100 performance, workload, and situational awareness measures. It offers an overview of measurement issues and presents descriptions, strengths and limitations.